Catheter Ablation Related Mitral Valve Injury: The Importance of Early Recognition and Rescue Mitral Valve Repair. (6th June 2014) - DESIMONE, CHRISTOPHER V.; HU, TIFFANY; EBRILLE, ELISA; SYED, FAISAL F.; VAIDYA, VAIBHAV R.; CHA, YONG‐MEI; VALVERDE, ARTURO M.; FRIEDMAN, PAUL A.; SURI, RAKESH M.; ASIRVATHAM, SAMUEL J.
Mitral Valve Injury with Catheter Ablation Introduction An increasing number of catheter ablations involve the mitral annular region and valve apparatus, increasing the risk of catheter interaction with the mitral valve (MV) complex. We review our experience with catheter ablation‐related MV injury resulting in severe mitral regurgitation (MR) to delineate mechanisms of injury and outcomes. Methods We searched the Mayo Clinic MV surgical database over a 19‐year period (1993–2012) and the electrophysiologic procedures database over a 23‐year period (1990–2013) and identified 9 patients with catheter ablation related MV injury requiring clinical intervention. Results Indications for ablation included atrial fibrillation (AF) [n = 4], ventricular tachycardia (VT) [n = 3], and left‐sided accessory pathways [n = 2]. In all 4 AF patients, a circular mapping catheter entrapped in the MV apparatus was responsible for severe MR. In all 3 VT patients, radiofrequency energy delivery led to direct injury to the MV apparatus. In the 2 patients with accessory pathways, both mechanisms were involved (1 per patient). Six patients required surgical intervention (5 MV repair, 1 catheter removal). One patient developed severe functional MR upon successful endovascular catheter disentanglement that improved spontaneously. Two VT patients with persistent severe postablation MR were managed nonsurgically, 1 of whom died 3 months postprocedure. Conclusion Circular mapping catheter entrapment and ablation at the mitral annulus are the most common etiologies of MV injury during catheter ablation. Close surveillance of the MV is needed during such procedures and early surgical repair is important for successful salvage if significant injury occurs.